Adhesive graphene grown on bioceramics with photothermal property. (September 2020) - Shen, A.; Zhao, C.; Mao, L.; Wu, Y.; Zhao, B.; Lin, K.
Abstract: Recently, graphene has been applied to modify biomaterials due to excellent physicochemical property and biocompatibility. However, some problems still exist especially the weak binding force between graphene and other biomaterials. Herein, a promising platform with photothermal property was constructed by fabricating the adhesive graphene in situ on the surface of β-tricalcium phosphate (β-Ca3 (PO4 )2, β-TCP) bioceramics using chemical vapor deposition (CVD). The result of ultrasonic cleaning treatment of graphene modified β-TCP (G-TCP) demonstrated that the prepared graphene coating could firmly modified on β-TCP due to the occurrence of carbothermal reduction on the ceramic surface to promote the nucleation and growth of graphene. G-TCP composites exhibited excellent photothermal effects when irradiated with 808 nm near-infrared laser (NIR). The photothermal effect of G-TCP composites could induce more than 90% of osteosarcoma cell (MNNG) death in vitro . These results confirmed that the graphene could be successfully fabricated in situ on the surface of β-TCP by CVD method, and exhibited high firmness and excellent photothermal performance, revealing a promising application in the photothermal therapy of bone tumors. Highlights: Graphene growing on bioceramics via CVD method without using any catalysts. The prepared graphene film adhesion strongly on the bioceramics. The prepared graphene film exhibition excellent photothermal effects.